Multiple Symmetric Lipomatosis (Madelung Disease) in a Large Canadian Family With the Mitochondrial MTTK c.8344A>G Variant - Perera, Uththara (J Investig Med High Impact Case Rep, 2018)
Background. Multiple symmetric lipomatosis (MSL), also known as Madelung disease, is a rare adult-onset disorder characterized by benign lipomatosis usually localized to the nuchal and upper thoracic region. A subset of these patients has germline variants in mitochondrial DNA. Methods. Three siblings of Northern European descent with MSL were assessed initially and provided whole blood for DNA analysis. Family history revealed several additional affected siblings who were dispersed across Canada. Targeted histories were obtained from 6 additional affected family members by telephone interviews using a standardized questionnaire, and genomic DNA was obtained from saliva. Sequencing of mitochondrial DNA was performed. Genetic analysis. Eight affected individuals who were studied each had the MTTK gene c.8344A>G variant. None of the affected individuals had epilepsy, ataxia, or myopathy. Conclusion. In this extended Canadian family, the rare MTTK c.8344A>G variant was linked with Madelung disease in multiple family members. Knowing the likely basis of MSL in this family may help with diagnosis, genetic counseling, monitoring for associated phenotypes, and potential future targeted interventions.